Comparing Cerebral White Matter, Cerebellar, and Pontine Reference Regions to Characterize Florbetapir Pet Measurements of Amyloid-β; Burden in Psen1 E280A Mutation Carriers and Noncarriers from the Colombian Autosomal Dominant Alzheimer's Disease Kindred (2018)
COL0010744